Method Of Using Physical Exercises For High School Age Children With Scoliosis (Texas Journal of Multidisciplinary Studies, 2024)
In this article, guidelines for organizing a physical education lesson for schoolchildren with scoliosis are mentioned. It is explained what exercises are appropriate for students with curvature of the spine. The need to refrain from certain prohibited actions is indicated.